A systematic review of Indigenous parents' educational engagement. Issue 2 (26th July 2022) - Sianturi, Murni; Lee, Jung‐Sook; Cumming, Therese M.
Abstract: The vital role of parents in Indigenous children's education has long been recognised in the school system; however, there is still limited understanding of the complex challenges experienced by parents in their educational engagement. This systematic review synthesised evidence from 41 studies to provide an understanding of Indigenous parents' perceptions about their educational engagement and strategies used by schools to facilitate their engagement. By employing a qualitative thematic synthesis, we identified three main themes: (1) the self‐perceived roles of Indigenous parents; (2) factors that hinder educational engagement; and (3) strategies that can support Indigenous parents. The findings suggest that cultural issues greatly influence the way parents perceive their role and are at the root of the hindering factors and effective strategies for increasing parental engagement. Schools' personnel can create opportunities for authentic collaboration with parents by undertaking a comprehensive identification of impeding factors and employing a strength‐based framework that acknowledges the importance of integrating cultural aspects and culturally responsive approaches. Context and implications Rationale for this study: Indigenous parental engagement in schools has continued to be a concern. Although such engagement is widely recognised as essential, fundamental enablers of parental engagement are not thoroughly examined. This study aimed to explore how home‐school relations could be established in ways that accommodate the preferences of Indigenous parents. Why do the new findings matter: This study provides a comprehensive analysis of how home‐school partnerships could be undertaken to produce an authentic collaboration between schools and Indigenous parents. The findings contribute to the body of knowledge about the factors hindering Indigenous parental engagement and culturally responsive strategies to enhance it. Implications for practitioners and policy makers: With the recognition of Indigenous cultures, schools can strengthen their genuine commitments to build an authentic and inclusive collaboration with Indigenous parents by empowering parents to engage in their children's education, building culturally responsive relationships with parents, and supporting the whole family and students' development. Moreover, policy makers might comprehensively investigate any culturally inappropriate and unsafe regulations in the existing policies and consider holistic programmes that are more culturally responsive.